PERBANDINGAN HARGA SAHAM DAN VOLUME PERDAGANGAN SAHAM SEBELUM DAN SAAT COVID-19 Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Septi Muzdalifah; Maslichah Maslichah (e_Jurnal Ilmiah Riset Akuntansi, 2021)
The purpose of this research is to find out and explain the comparison of stock prices and stock trading volume before and during Covid-19 in manufacturing companies in the consumer good industry sector which are listed on the Indonesia Stock Exchange. The sample selection in this study was carried out using purposive sampling method with several specified sample criteria in order to obtain a sample of 49 companies. The data used in this study is secondary data, namely in the form of daily reports of each company that issues data on share prices and share trading volume. Then the data analysis techniques used in this research are descriptive statistics, normality test and hypothesis testing.The results in this study explain that stock prices and share trading volume show that there are significant differences before and during the Covid-19 incident, in this study it shows that stock prices have decreased after the Covid-19 incident, while the volume of stock trading has increased. after the Covid-19 incident.Keywords: Stock price, share trading volume, Covid-19.